Anlotinib combined with osimertinib reverses acquired osimertinib resistance in NSCLC by targeting the c-MET/MYC/AXL axis. (February 2023) - Lei, Tianyao; Xu, Tianwei; Zhang, Niu; Zou, Xiaoteng; Kong, Ziyue; Wei, Chenchen; Wang, Zhaoxia
Abstract: Favorable clinical evidence suggests that the next trend in new treatments for advanced non-small cell lung cancer (NSCLC) will be combination therapies. However, inevitable epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) resistance greatly limits the clinical efficacy of patients carrying EGFR-activating mutants. In this study, we found a patient with clinical osimertinib resistance who regained a positive response after osimertinib plus anlotinib treatment. Two osimertinib-resistant cell lines were constructed, and AXL conferred resistance to osimertinib in NSCLC cell lines. The combined effects of anlotinib and osimertinib restored sensitivity to osimertinib in two osimertinib-resistant NSCLC cell lines and in xenografts. Moreover, anlotinib inhibits the phosphorylation of AXL in both resistant cell lines. Mechanistically, we confirmed that MYC binds to the promoter of AXL to promote its transcription in NSCLC cells, and we demonstrated that anlotinib combined with osimertinib treatment enhances the anti-tumor effect by inactivating the c-MET/MYC/AXL axis to reverse osimertinib resistance in NSCLC. In conclusion, our results provide strong support that this combination therapy may be effective in enhancing the efficacy of treatments in patients with advanced NSCLC. Graphical Abstract: ga1 Highlights: Inevitable acquired EGFR-TKIs resistance greatly limits the clinical efficacy. AXL confers intrinsic resistance to osimertinib in osimertinib-resistant cells. Anlotinib combined with osimertinib sensitizes osimertinib resistance both in vitro and in vivo. AXL is a crucial effector underlying the effectiveness of co-treatment on osimertinib-resistant cell lines. Anlotinib combined with osimertinib reverses osimertinib resistance by targeting the c-MET/MYC/AXL axis in NSCLC.